2013
DOI: 10.1007/s00395-013-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induces senescence and impairs function of human cardiac progenitor cells

Abstract: The increasing population of cancer survivors faces considerable morbidity and mortality due to late effects of the antineoplastic therapy. Cardiotoxicity is a major limiting factor of therapy with doxorubicin (DOXO), the most effective anthracycline, and is characterized by a dilated cardiomyopathy that can develop even years after treatment. Studies in animals have proposed the cardiac progenitor cells (CPCs) as the cellular target responsible for DOXO-induced cardiomyopathy but the relevance of these observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 60 publications
9
134
0
Order By: Relevance
“…It has been assumed that the loss of a chemokine/GF gradient within the healed myocardium may be responsible for the lack of endogenous repair despite an actual increase of tissue CPCs (58,64,82). Our results on BrdU incorporation and Ki-67 labeling support the contention that more robust myocardial regeneration, compared with untreated MI, can be obtained via all three regenerative therapies, which may reverse the unfavorable microenvironment and promote the repairing ability of CPCs either resident or locally injected.…”
Section: Cardiac Regeneration Anatomy and Mechanicssupporting
confidence: 71%
“…It has been assumed that the loss of a chemokine/GF gradient within the healed myocardium may be responsible for the lack of endogenous repair despite an actual increase of tissue CPCs (58,64,82). Our results on BrdU incorporation and Ki-67 labeling support the contention that more robust myocardial regeneration, compared with untreated MI, can be obtained via all three regenerative therapies, which may reverse the unfavorable microenvironment and promote the repairing ability of CPCs either resident or locally injected.…”
Section: Cardiac Regeneration Anatomy and Mechanicssupporting
confidence: 71%
“…This has been intensified by recognition that Mfn2 may play a critical role in cell‐based therapies promoting the differentiation of stem cells into cardiomyocytes (Kasahara et al, 2013; Suliman et al, 2016). Indeed, DOX‐induced cardiomyopathy is associated with depletion and senescence of the cardiac progenitor cell pool in both rat and human hearts, permanently impairing their function (de Angelis et al, 2010; Piegari et al, 2013). Therefore, a pharmacological strategy involving Mfn2 that could potentially prevent degeneration of both adult cardiac cells and the resident stem cell pool seems an attractive idea.…”
Section: Discussionmentioning
confidence: 99%
“…In a juvenile mouse model treated with DOX, the development of an abnormal vasculature resulted in higher susceptibility to myocardial infarction. Also, a decreased number of CPCs was observed after DOX treatment, suggesting that these undifferentiated cells are more susceptible to DOX, thus limiting the resistance of the treated heart to oxidative stress [9,59]. According to this, Angelis et al reported also that adult and neonatal rat cardiomyocytes have different susceptibilities to DOX exposure, with the apoptotic pathway being more active in immature cells [60].…”
Section: Discussionmentioning
confidence: 97%
“…CPCs have been studied in the context of several pathological conditions in animal and humans including as a pathophysiological target against DOX cardiotoxicity [9][10][11][12]. One relevant model to investigate DOXinduced effects on CPCs is the H9c2 cell line, which has morphological characteristics similar to immature embryonic cardiomyocytes [2,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation